Efektivitas Kinerja BAN-PDM Pasca Restrukturisasi Organisasi: Studi Penggabungan BAN-PAUD dan BAN-SM di Provinsi Lampung - Saputra, Kurnia Andi; Prihantika, Ita (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2025)
Organizational structure change is an important strategy to improve work effectiveness and efficiency, including in the education sector. This study aims to analyze the effect of organizational restructuring on the effectiveness of the National Accreditation Board for Early Childhood, Primary and Secondary Education (BAN-PDM) of Lampung Province in carrying out its duties and functions. The method used is explanatory research with a quantitative approach, and the sampling technique used is saturation sampling because the population is small, namely 17 members and staff of BAN-PDM. Data were collected through questionnaires and analyzed using validity tests, reliability, descriptive statistics, classical assumption tests, and simple linear regression. The results of the study indicate that organizational restructuring has a positive and significant effect on the effectiveness of BAN-PDM performance, which includes changes in structure, technology, and human resources after the merger of BAN-PAUD and BAN-SM. This study emphasizes the importance of effective change management so that organizational effectiveness can continue to be improved.